The role of principal transformational leadership in implementing character education in public Elementary Schools of Kotagede subdistrict - Sapitri, Riris; Purwanto, Nurtanio Agus (Educenter : Jurnal Ilmiah Pendidikan, 2025)
A preliminary study found that qualitative findings revealed a gap between expectations and reality in the transformational leadership of school principals in implementing character education. Principals were not consistently setting a good example for students, teachers, staff, or parents, resulting in suboptimal implementation of character education. This study aims to describe the implementation of character education in the Pancasila Student Profile and analyze the principal’s role in providing ideal influence, inspirational motivation, intellectual stimulation, and individualized consideration. It also identifies the driving and inhibiting factors in the implementation of character education at SDN Kotagede 5. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation, with validity tested using credibility, transferability, dependability, and confirmability. The findings show that character education has been well implemented across learning, school culture, and extracurricular activities, covering six dimensions of the Pancasila Student Profile. The study concludes that the principal’s transformational leadership plays a strategic role in creating a supportive environment, though challenges remain in student discipline and school coordination. Strengthening teacher appreciation, parental involvement, and student mentoring strategies are recommended to improve effectiveness.